일본 와인산업의 현황과 과제 - 김성각 (일본 야마가타대학, 2003)
The wine market of Japan has been expanding rapidly with its developing economy since 1970s . Now the Japan wine market represents a very high seller concentration and is under the control of a few of big scale wine makers. Moreover Japan wine industry has largely depended on the imported wine & raw materials and such trends is getting stronger recently under the name of cost saving and quality improvement of Japan wine. However, there are a lot of small and medium scale wine makers in Japan, which has been trying to make an original Japan Wine for a long time. In this paper, such medium scale wine makers are analyzed mainly focusing on how they acquire raw grape and market their wine.
Keywords: 일본; 와인산업; 중견 와인메커; Japan; Wine Industry; Medium scale wine makers